A household optimum utility approach for modeling joint activity-travel choices in congested road networks. (April 2020) - Vo, Khoa D.; Lam, William H.K.; Chen, Anthony; Shao, Hu
Highlights: Propose a new household activity-based network equilibrium model that takes into account the interactions between household members by heterogeneous household type with different size for making choices on daily joint/solo activities and travel in congested road networks. Introduce two new household-oriented network equilibrium principles based on household optimum and household-based system optimum, together with the formulations of their equivalent mathematical programming problems, and their analytical relationships to the conventional user equilibrium (individual optimum) and individual-based system optimum. Propose a new supernetwork platform for converting the time-dependent household daily activity-travel scheduling problem into an equivalent static traffic assignment problem within a unified modeling framework. Provide two numerical examples to illustrate the merits of the proposed model together with the key insights from the results. Abstract: This study proposes a new household optimum (HO) utility approach to model the intra-household interactions between household members by heterogeneous household type with different size in deciding their daily joint/solo activities and travel in congested road networks. In contrast to the conventional approach based on selfish choices of individuals to maximize their own utility, the proposed approach considers the activity-travel choices of all household members to maximize their household utility. Based on the HO utility approach, a new household activity-based network equilibrium model is proposed to simultaneously take into account the time-dependent household daily activity-travel scheduling and traffic assignment problems within a unified modeling framework. Two new household-oriented network equilibrium principles, namely, HO and household-based system optimum (HSO), are introduced together with the formulations of their equivalent mathematical programming problems. The analytical relationships between HO, HSO, conventional user equilibrium and individual-based system optimum, and their properties are then investigated. The proposed model is formulated as an equivalent variational inequality problem and solved by a diagonalization method in a supernetwork platform. Numerical examples are provided to illustrate the merits of the proposed model, together with the key insights of the results that highlight the importance of considering joint activities and travel in travel demand forecasting and transportation network design.